2011
DOI: 10.1021/jz2013193
|View full text |Cite
|
Sign up to set email alerts
|

Sequestering High-Energy Electrons to Facilitate Photocatalytic Hydrogen Generation in CdSe/CdS Nanocrystals

Abstract: The photocatalytic H2O splitting activities of CdSe and CdSe/CdS core/shell quantum dots are contrasted. CdSe/CdS core/shell quantum dots constructed from 4.0 nm CdSe quantum dots are shown to be strongly active for visible-light-driven photocatalytic H2 evolution in 0.1 M Na2S/Na2SO3 solution with a turnover number of 9.94 after 5 h at 103.9 μmol/h. CdSe quantum dots themselves are only marginally active in 0.1 M Na2S/Na2SO3 solution with a turnover number of 1.10 after 5 h at 11.53 μmol/h, while CdSe quantum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(83 citation statements)
references
References 50 publications
(107 reference statements)
5
77
1
Order By: Relevance
“…As expected, core/shell QDs present increased overall efficiency both in the rate of H 2 production as well as in stability. 1036,1037 If the overall absorbance of the QD is maintained as a constant, then a thicker shell (CdS) appears preferable to a larger core (CdSe). 1036 One example of an "outside the box" core/shell structure substituted a thin layer of α-TiO 2 as the shell on CdSe QDs (Figure 147).…”
Section: Hydrogen Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, core/shell QDs present increased overall efficiency both in the rate of H 2 production as well as in stability. 1036,1037 If the overall absorbance of the QD is maintained as a constant, then a thicker shell (CdS) appears preferable to a larger core (CdSe). 1036 One example of an "outside the box" core/shell structure substituted a thin layer of α-TiO 2 as the shell on CdSe QDs (Figure 147).…”
Section: Hydrogen Productionmentioning
confidence: 99%
“…1036,1037 If the overall absorbance of the QD is maintained as a constant, then a thicker shell (CdS) appears preferable to a larger core (CdSe). 1036 One example of an "outside the box" core/shell structure substituted a thin layer of α-TiO 2 as the shell on CdSe QDs (Figure 147). 1038 The inclusion of the α-TiO 2 creates a band offset in the conduction band of the CdSe, where the electron can transfer to the shell improving charge separation and resulting in an increase in H 2 production from 89 to 240 μmol g −1 h −1 .…”
Section: Hydrogen Productionmentioning
confidence: 99%
“…33 More importantly, the core/shell configuration is thought to help sequester high-energy electrons to facilitate H 2 photogeneration because the photoexcited electrons must tunnel through the CdS-shell and initiate redox chemistry on the surface, which does not adversely hinder photoactivity because the redox time scale is significantly longer than the tunneling time scale. 33 Small satellite Au NPs were prepared by Au deposition on the surface of CdSe/CdS NCs by aging the mixture of QDs and Au(3+)-dodecylamine (DDA) precursor in toluene for 1 h. Extra reducing agent was not necessary in the reaction system since DDA could reduce Au 3+ sufficiently in the presence of S-NCs. 34 It is impossible to prepare QD/Au core/ shell nanocrystals by our experiment method, although we increase the amount of Au precursor during the preparation, the as-prepared nanoparticles are still core−satellite heteronanocrystals but not QD/Au core/shell structure.…”
Section: Methodsmentioning
confidence: 99%
“…The hierarchical core-shell metal sulfide nanoarchitectures present an important candidate for the application in photocatalytic H 2 evolution. For instance, the enhanced H 2 -evolution activity was observed in the core-shell structured CdSe/ CdS [173] or CdS/ZnS [172,174] system due to the passivation effects of shell layer. Recently, Cheng et al demonstrated that the mesoporous ZnS shell in the hierarchical CdS-ZnS core-shell particles can promote the unique spatial distribution of the photoexcited charge carriers and thus greatly enhance the hydrogen evolution rate, which is 169 and 56 times higher than those of ZnS and CdS under visible light, respectively [174].…”
Section: Developing Core/shell and Intercalated Semiconductorsmentioning
confidence: 99%